Anatomical human fitting of the BiVACOR total artificial heart. Issue 1 (4th October 2021) - Emmanuel, Sam; Jansz, Paul; McGiffin, David; Kure, Christina; Watson, Alasdair; Connellan, Mark; Granger, Emily; Iyer, Arjun; Timms, Daniel; Hayward, Christopher
Abstract: Background: BiVACOR is a novel total artificial heart (TAH) utilizing a single centrifugal magnetically levitated rotor with the ability to modulate pulsatile flow. The device has been successfully tested in a bovine model. We undertook a multicenter anatomical and virtual fitting study of the BiVACOR in patients undergoing heart transplantation. Methods: 10 patients were recruited across two heart transplant centers. A sterilized 1:1 titanium model of the device was inserted into the patient's chest post heart explant, prior to implantation of the donor heart. Measurements were recorded in situ. The device was then removed. Following this, retrospective 3D reconstructions were created from computed tomography chest scans to simulate a virtual fitting. Results: Mean age was 53 years (range 38–67). Mean BMI was 28 (range 20–37). Heart failure etiology was varied—with ischemic cardiomyopathy being the most common. Mean spine‐to‐sternum distance at the tenth thoracic vertebrae (T10) was 14 cm (range 11–18). Mean aorta to aortic Port distance was 0.2 cm (range 0–0.5). Mean pulmonary artery to pulmonary artery port distance was 4.2 cm (range 1–7). The device fitted suitably in all patients without gross distortion to the geometry between native vessel/chamber and port. Conclusions: This study described the anatomical and virtual fitting of the BiVACOR TAH. The device fit well within the chest cavities of all 10 patients, who represented a variety of body morphologies and heart failure etiology. Abstract : Model of the BiVACOR total artifical heart